2018
DOI: 10.1093/hmg/ddy439
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fgf10 deficiency on pulmonary vasculature formation in a mouse model of bronchopulmonary dysplasia

Abstract: Bronchopulmonary dysplasia (BPD), characterized by alveoli simplification and dysmorphic pulmonary microvasculature, is a chronic lung disease affecting prematurely born infants. Pulmonary hypertension (PH) is an important BPD feature associated with morbidity and mortality. In human BPD, inf lammation leads to decreased fibroblast growth factor 10 (FGF10) expression but the impact on the vasculature is so far unknown. We used lungs from Fgf10 +/− versus Fgf10 +/+ pups to investigate the effect of Fgf10 defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Bhatt et al analyzed lung samples from infants who died with BPD versus infants who died from non-pulmonary causes and found a decreased expression of VEGF and platelet endothelial cell adhesion molecule-1 (PECAM, also termed CD31, endothelial marker), as well as a decreased staining density of alveolar capillaries in BPD infants, indicating that the development of the pulmonary microvasculature was disrupted in BPD patients [ 4 ]. Consistent with previous results, we and others, utilizing BPD animal models, established by hyperoxia exposure, also showed a decrease of endothelial cells in capillaries and blood vessel numbers and an increase of α-Sma positive cells (VSMC) in the tunica media of pulmonary arterioles and normally non-muscularized precapillary arterioles [ 79 , 80 , 81 ]. A lineage tracing study indicated that the expansion of resident SMCs was the major source related to the thickening of the smooth muscle layer in adult PH [ 82 ].…”
Section: Development Of Normal Pulmonary Vasculature and Bpd-ph Frsupporting
confidence: 92%
See 2 more Smart Citations
“…Bhatt et al analyzed lung samples from infants who died with BPD versus infants who died from non-pulmonary causes and found a decreased expression of VEGF and platelet endothelial cell adhesion molecule-1 (PECAM, also termed CD31, endothelial marker), as well as a decreased staining density of alveolar capillaries in BPD infants, indicating that the development of the pulmonary microvasculature was disrupted in BPD patients [ 4 ]. Consistent with previous results, we and others, utilizing BPD animal models, established by hyperoxia exposure, also showed a decrease of endothelial cells in capillaries and blood vessel numbers and an increase of α-Sma positive cells (VSMC) in the tunica media of pulmonary arterioles and normally non-muscularized precapillary arterioles [ 79 , 80 , 81 ]. A lineage tracing study indicated that the expansion of resident SMCs was the major source related to the thickening of the smooth muscle layer in adult PH [ 82 ].…”
Section: Development Of Normal Pulmonary Vasculature and Bpd-ph Frsupporting
confidence: 92%
“…A BPD-PH animal model needs to be established. It has been shown recently, that blockade of Fgfr2b ligands activity postnatally in a BPD mouse model lead to decreased blood vessel number and increased muscularization resembling a PH-like phenotype [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a developmental point of view, this phenotype is caused by impaired formation of secondary septa which are transient structures leading to the subdivision of the sacs into smaller units called alveoli. Our mouse data suggest that Fgf10 is indeed critical for the alveologenesis phase to occur and has also a collateral impact on the formation of the vascular system (Chao et al, 2019). Therefore, while the role of Fgf10 appears to be consistent between human and mouse during alveologenesis, we recently reported that FGF10 displayed a discordant role in lung branching morphogenesis in human and mouse (Danopoulos et al, 2019).…”
mentioning
confidence: 57%
“…In addition, during embryonic development, mesenchymal cells expressing FGF10 are progenitors for airway and vascular SMC [ 59 ]. VEGFa is a target of FGF10 in developing lung epithelium and the reduction in FGF10 levels leads to decrease in VEGFa and vascular defect [ 60 ]. FGF10 is not only essential for epithelial progenitor cell proliferation but also for coordinated alveolar SMC formation and vascular development [ 61 ].…”
Section: Deregulated Signaling Pathwaysmentioning
confidence: 99%